Healthcare Workers Occupationally Exposed to Ionizing Radiation Exhibit Altered Levels of Inflammatory Cytokines and Redox Parameters - Iman M. Ahmad; Maher Y. Abdalla; Tiffany A. Moore; Lisa Bartenhagen; Adam J. Case; Matthew C. Zimmerman (MDPI AG, 2019)
Studies have shown an increased risk for a variety of cancers, specifically brain cancer, in healthcare workers occupationally exposed to ionizing radiation. Although the mechanisms mediating these phenomena are not fully understood, ionizing radiation-mediated elevated levels of reactive oxygen species (ROS), oxidative DNA damage, and immune modulation are likely involved. A group of 20 radiation exposed workers and 40 sex- and age-matched non-exposed control subjects were recruited for the study. We measured superoxide (O2•−) levels in whole blood of healthcare workers and all other measurements of cytokines, oxidative DNA damage, extracellular superoxide dismutase (EcSOD) activity and reduced/oxidized glutathione ratio (GSH/GSSG) in plasma. Levels of O2•− were significantly higher in radiation exposed workers compared to control. Similarly, a significant increase in the levels of interleukin (IL)-6, IL-1α and macrophage inflammatory protein (MIP)-1α in radiation exposed workers compared to control was observed, while there was no significance difference in the other 27 screened cytokines. A significant positive correlation was found between MIP-1α and O2•− levels with no correlation in either IL-6 or IL-1α. Further, a dose-dependent relationship with significant O2•− production and immune alterations in radiation exposed workers was demonstrated. There was no statistical difference between the groups in terms of oxidative DNA damage, GSH/GSSG levels, or EcSOD activity. Although the biologic significance of cytokines alterations in radiation exposed workers is unclear, further studies are needed for determining the underlying mechanism of their elevation.